QURAISY DAN HEGEMONI KUASA ATAS AGAMA; Studi Analitis Ilmu Hadis dan Sosial - Muhamad Ridwan Nurrohman (Diroyah : Jurnal Studi Ilmu Hadis, 2018)
This paper aims to re-examine one of the themes in the Prophet's hadith, namely "al-aimmatu min Quraish". Ahlu Sunnah, understand the point "descendants of Quraysh" in the preconditions of Imamat as an ijma '. Although this does not close the opportunity to present thinkers who reject the consensus. But when testing this hadith in terms of hadith, social, and historical reality. It is proven that what is a sunnah consensus is not a blind dogma, let alone merely a political tool. But it is another sign, the truth of Muhammad's prophethood.